2016
DOI: 10.1021/acsami.6b15034
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Performance Depending on Morphology of Bismuth Vanadate Thin Film Synthesized by Pulsed Laser Deposition

Abstract: We have fabricated high quality bismuth vanadate (BiVO) polycrystalline thin films as photoanodes by pulsed laser deposition (PLD) without a postannealing process. The structure of the grown films is the photocatalytically active phase of scheelite-monoclinic BiVO which was obtained by X-ray diffraction (XRD) analysis. The change of surface morphology for the BIVO thin films depending on growth temperature during synthesis has been observed by scanning electron microscopy (SEM), and its influence on water spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 25 publications
5
32
0
Order By: Relevance
“…ratios in B, LB, BC, and BCL are calculated to be 3.51, 1.26, 8.86, and 1.92, respectively. No unwanted vanadate phase is present in B prepared at a relatively lower temperature . The XRD pattern is enclosed by (003), (006), (009), (015), (012), (110), and (113) crystal planes of L and can be assigned to ICDD card no.…”
Section: Resultsmentioning
confidence: 99%
“…ratios in B, LB, BC, and BCL are calculated to be 3.51, 1.26, 8.86, and 1.92, respectively. No unwanted vanadate phase is present in B prepared at a relatively lower temperature . The XRD pattern is enclosed by (003), (006), (009), (015), (012), (110), and (113) crystal planes of L and can be assigned to ICDD card no.…”
Section: Resultsmentioning
confidence: 99%
“…The sputtering conditions during PLD strongly affect the properties of the resulting layer [17]. It was shown that pulsed laser deposited BiVO 4 films on FTO substrates obtained at 230 • C can generate high photocurrents equal to about 3 mA cm −2 , but only in the hole-scavenger containing electrolyte [18]. Other authors showed that the high temperature (500 • C) in the deposition chamber makes the growth of BiVO 4 crystallites anisotropic [19].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of such efforts, a few candidates have been introduced and investigated extensively. The promising candidates are BiVO 4 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], Fe 2 O 3 [25][26][27][28][29][30][31][32], and BiFeO 3 [33][34][35]. Figure 2 shows the band gap energies and band edge positions of various semiconductors with respect to the water redox potential.…”
Section: Absorption Of Solar Radiationmentioning
confidence: 99%
“…In order to solve the problem, some solutions have been introduced, such as increasing the density of surface active sites or combining them with oxygen evolution co-catalysts (OECs). Recently, our group reported on the deposition of a high quality polycrystalline BiVO 4 photoanode with a controllable surface area [10]. The BiVO 4 film was grown by pulsed laser deposition (PLD), and the surface area of film was optimized by controlling process temperatures during growth of the BiVO 4 .…”
Section: Of 16mentioning
confidence: 99%